Celiac Disease in Conjunction with Hereditary Fructose Intolerance as a Rare Cause of Liver Steatosis with Mild Hypertransaminasemia-A Case Report - Anna Bobrus-Chociej; Agnieszka Pollak; Natalia Kopiczko; Marta Flisiak-Jackiewicz; Rafał Płoski; Dariusz M. Lebensztejn (MDPI AG, 2021)
Celiac disease (CD) has been associated with several genetic and autoimmune disorders, but its association with hereditary fructose intolerance (HFI) is very rare. The possibility of an association between CD and HFI should be considered, especially in patients with a lack of improvement after a gluten-free diet. Children with HFI often present with a wide range of symptoms, however, data about a strong aversion to fruits and sweets may be helpful to establish the diagnosis. The diagnosis of HFI should be confirmed in genetic testing. Both CD and HFI may present with liver steatosis with hypertransaminasemia. In patients with these two disorders, the dietary restrictions of gluten and fructose improve clinical symptoms and protect them from secondary complications. We report the case of a child with the concurrence of these two disorders.